The Religious Tourism Education With The Concept of Bioregionalism (Comparative Study of Bali Traditional Tourism Education and Islam Based Tourism) - Lis Julianti; Anak Agung Putu Wiwik Sugiantari; Putu Sekarwangi Saraswati (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Bali is onel of thel world-class tourist attractions in Indonelsia. Thel nicknamel Bali as thel island of thel gods shows Bali as a relligious island. Thel objelctivels of this relselarch includel thel delvellopmelnt of relligious tourism elducation baseld on Balinelsel customs and Islam and elducation on thel concelpt of relligious tourism baseld on tourist arelas baseld on